Injectable trace minerals administration to beef cattle at arrival: effects on growth performance, respiratory disease and serum antioxidant status - Silvia Grossi; Riccardo Compiani; Marcello Guadagnini; Andrea Rosati; Carlo Angelo Sgoifo Rossi (Italian Journal of Animal Science)
The application of injectable zinc, copper, manganese and selenium (trace minerals - ITMs) at the arrival can be a strategy to boost the antioxidant defences and immune function, with positive effects on production performances, in fattening beef cattle. The effects of the administration of ITMs at the arrival were tested in 576 Charolaise bulls, randomly allocated, at the arrival, into two groups, i) control (CON); ii) Multimin (MM-Multimin®). The growth performance, feed intake (FI), feed conversion ratio (FCR), and health status were evaluated. The oxidative status was evaluated using the levels of free oxygen radical metabolites (ROM’s), and the antioxidant activity (OXY test) on blood samples taken on 20 animals per group at the arrival (d0), and after 50 days (d50). MM animals had significantly improved average daily gain (ADG0-50) (1.244 vs 1.201 kg/head/d) (p = 0.002), final weight at d50 (448 vs 446 kg) (p = 0.0203) and feed conversion rate (FCR) (6.90 vs 7.52) (p < 0.0001) compared to CON, with a tendency towards a significantly lower individual feed intake (FI) (8.46 vs 8.66 kg/head/d) (p = 0.0558). The incidence of BRD, was not significantly affected by the treatment. The antioxidant activity at d50 was significantly improved (280.34 vs 270.51 HClO/ml) (p ≤ 0.001) in the MM compared to the CON group. No differences were found for ROM’s levels. The results highlight the potential benefits of an ITMs product application on arrival at the fattening unit, aiming to boost the antioxidant defences with positive effects on growth performance.